Fluorescent bacteria producers of metabolitos antagónicos de cultivares nativos de Musa sp. And their phylogenetic diversity the 16S rRNA gene - Martínez, Hayron Fabricio (2018)
The objective of the work was to identify fluorescent bacteria producing antagonistic secondary metabolites and analyze their biodiversity to the 16S rRNA gene. The bacteria were isolated from native Musa cultivars of the provinces: Los Ríos, Cotopaxi and Bolívar. The screening of the antagonistic strains was based on the proteolytic activity and the amplification of antifungal genes. Further, phylogenetic analysis was performed on 16S ribosomal RNA by ARDRA restriction analysis and sequencing. From the rhizosphere of seven native Musa cultivars, 16 native strains with fluorescent emission were rescued and selected, observing the protease activity (PR) for the strains (PB3-6, BO3-4, BA4-19, PM3-8 and PM3-14). Verifying by PCR the presence of the hcnABC gene (HCN) of 570 bp in the strains (PB3-6, BO3-4, PM3-8 and PM3-14) and pyrrolnitrine (Prn) of 786 bp in the strains (BMR2-2, BMR2-4, BMR2-12, BO3-4 and PM3-14). The genetic profiles by ARDRA grouped the native strains of Musa producers to PR, Prn and HCN (BMR2-2, BMR2-12, PB3-6, BO3-4, BA4-19, PM3-8 and PM3-14). The molecular characterization by sequencing of the 16S rRNA gene, the genera were verified: Serratia, Pseudomonas, Acinetobacter, Enterobacter and Klebsiella. Considering seven strains of candidate bacteria of antagonistic activity that will serve for the continuity of the research to the positive effect in increase of biomass in banana plantations and biocontrol effect to Mycosphaerella fijiensis.